Hormonal Predictors of Abnormal Luteal Phases in Normally Cycling Women - Abdulla, Saman H.; Bouchard, Thomas P.; Leiva, Rene A.; Boyle, Phil; Iwaz, Jean; Ecochard, René (Frontiers in Public Health, 2018)
Objective: Explore potential relationships between preovulatory, periovulatory, and luteal-phase characteristics in normally cycling women. Design: Observational study. Setting: Eight European natural family planning clinics. Patient(s): Ninety-nine women contributing 266 menstrual cycles. Intervention(s): The participants collected first morning urine samples that were analyzed for estrone-3 glucuronide (E1G), pregnanediol-3- alpha-glucuronide (PDG), follicle stimulating hormone (FSH), and luteinizing hormone (LH). The participants underwent serial ovarian ultrasound examinations. Main Outcome Measure(s): Four outcome measures were analyzed: short luteal phase, low mid-luteal phase PDG level (mPDG), normal then low luteal PDG level, low then normal luteal PDG level. Results: A long preovulatory phase was a predictor of short luteal phase, with or without adjustment for other variables. A high periovulatory PDG level was a predictor for short luteal phase as well as normal then low luteal PDG level. A low periovulatory PDG level predicted low mPDG and low then normal luteal PDG level, with or without adjustment for other variables. A small maximum follicle predicted normal then low luteal PDG level, with or without adjustment for other variables. The relationship between small maximum follicle size and short luteal phase or small maximum follicle size and low mPDG was no longer present when the regression was adjusted for certain characteristics. A younger age at menarche and a high body mass index were both predictors of low mPDG. Conclusion: Luteal phase abnormalities exist over a spectrum where some ovulation disorders may exist as deviations from the normal ovulatory process.This study confirms the negative impact of a small follicle size on the quality of the luteal phase. The occurrence of normal then low luteal PDG level is confirmed as a potential sign of luteal phase abnormality.